2022
DOI: 10.1371/journal.pone.0270759
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tonotopic matching and spatial cues on segregation of competing speech in simulations of bilateral cochlear implants

Abstract: In the clinical fitting of cochlear implants (CIs), the lowest input acoustic frequency is typically much lower than the characteristic frequency associated with the most apical electrode position, due to the limited electrode insertion depth. For bilateral CI users, electrode positions may differ across ears. However, the same acoustic-to-electrode frequency allocation table (FAT) is typically assigned to both ears. As such, bilateral CI users may experience both intra-aural frequency mismatch within each ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
1
0
0
Order By: Relevance
“…[28] found that SRM was approximately 5dB or more for ILDinf than for HTRF-based processing, for both actual bilateral CI listening and for bilateral CI simulations. Similar differences were observed in our previous studies (1.8dB SRM in [29] with HRTF vs. 7.6dB SRM in [15] with dichotic listening). Therefore, the present approach allows for better stimulus control, the largest possible differences between the diotic and dichotic performance, and potentially larger SRM so that the effects of inter-aural mismatch in the degree of channel interaction on SRM can be better exploited.…”
Section: Conditionssupporting
confidence: 92%
“…[28] found that SRM was approximately 5dB or more for ILDinf than for HTRF-based processing, for both actual bilateral CI listening and for bilateral CI simulations. Similar differences were observed in our previous studies (1.8dB SRM in [29] with HRTF vs. 7.6dB SRM in [15] with dichotic listening). Therefore, the present approach allows for better stimulus control, the largest possible differences between the diotic and dichotic performance, and potentially larger SRM so that the effects of inter-aural mismatch in the degree of channel interaction on SRM can be better exploited.…”
Section: Conditionssupporting
confidence: 92%